El matrimonio en Tierra de Campos Leonesa en el siglo XVIII: unión de personas y de patrimonios. - Francisco Javier Lagartos Pacho (Nuevo mundo - Mundos Nuevos, 2008)
Study and analysis, by means of the use of notarial registrations, of the different aspects related with the conformation of the patrimony of the married couple; it embraces from the moment in which a person begins to look for his/her future husband/wife until the marriage is actually realized with the effective union of people and patrimonies, during the XVIII century in Tierra de Campos Leonesa (District of Sahagún, León).